Biodegradation of di-n-octyl phthalate by Gordonia sp. Lff and its application in soil. Issue 17 (29th July 2022) - Wang, Yangyang; Ren, Qiang; Zhan, Wenhao; Zheng, Kaixuan; Liao, Qi; Yang, Zhihui; Wang, Yansong; Ruan, Xinling
ABSTRACT: A previous isolated Gordonia sp. (Lff) was used to degrade di-n-octyl phthalate (DOP) contamination in both aqueous solution and soil. The influence of temperature, pH, inoculum size, salt content and initial concentration of DOP on DOP degradation by Lff were analysed. The response of soil bacterial community to DOP and Lff was also analysed by Illumina MiSeq sequence method. Results showed that the optimal temperature, pH, inoculum size and salt content were 35 o C, 8.0, 5% and <5%, respectively. Under the optimal condition, more than 91.25% of DOP with different initial concentrations (100–2000 mg/L) could be degraded by Lff. Kinetics analysis indicated that biodegradation of DOP by Lff could be described by first-order kinetics ( R 2  > 0.917) with the half-life ( t 1/2 ) changing irregularly between 0.58 and 0.83 d. In addition, Lff enhanced the removal of DOP in soil and alleviated the toxicity of DOP on soil microorganisms. Furthermore, its influence on soil bacterial community is not obvious. These results suggested that Lff was effective in remediating DOP contamination in different environments. GRAPHICAL ABSTRACT: UF0001